PENGEMBANGAN APLIKASI MOBILE FEEDEZ SEBAGAI SISTEM KENDALI JARAK JAUH AUTOMATIC FISH FEEDER BERBASIS IOT: DEVELOPMENT OF THE FEEDEZ MOBILE APPLICATION AS AN IOT-BASED AUTOMATIC FISH FEEDER REMOTE CONTROL SYSTEM - Moh Fauzan Fakhira Nasihin; Nuur Wachid Abdul Majid (LPPM Universitas Abdurrab, 2026)
The application of Internet of Things (IoT) technology in the aquaculture sector continues to grow as an effort to improve the efficiency and precision of fish feeding. However, most of the automatic fish feeder systems that have been developed still rely on physical interfaces or third-party IoT platforms that have limitations in terms of customization and responsiveness. This study aims to develop an Android-based mobile application as a controller for automatic fish feeders, with a focus on improving the flexibility of mechanical settings and real-time control responsiveness. The research method used is the Prototyping software development model. The FeedEZ application was developed using React Native with the WebSocket communication protocol and integrated with Arduino Uno R3-based hardware and the ESP8266 module. Black box functional testing demonstrated the validity of all application features, while performance testing recorded an average end-to-end response time of 0.92 seconds with a standard deviation in the stable phase of 0.11. This response value is below the real-time interaction threshold (1 second), proving the system's effectiveness in providing instant control. This research demonstrates the paradigm of developing a full-stack custom IoT solution as a more flexible, standalone, and responsive alternative to the popular but limited platform-based approach.